Electricity market : growth, efficiency, and price discovery - Guo, Huicong (2016)
Our report evaluates the importance of efficiency in the electricity market in Singapore and how various regulatory instruments contribute to this efficiency. The report comprises of three main parts. Chapter 2 examines the Granger causality between energy and growth to understand the nature of the energy-growth causal relationship in Singapore. A bivariate model (of energy and income), a multivariate demand model (which uses energy, income, and energy price), and an augmented production model (which uses energy, income, capital, and labour) are used for the analysis. Three different energy metrics—Total Primary Energy Consumption (1980-2011), Total Primary Energy Supply (1990-2013), and Total Electricity Generation (1975-2014)—are used. The models are described using a Vector Error-Correction Model framework when possible. Otherwise a Vector Auto-Regression in first differences is used. As a whole, the Granger causality test results suggest that the conservation hypothesis holds in the Singapore, for both energy and electricity consumption.